PENGARUH PENGGUNAAN MEDIA TANGRAM TERHADAP HASIL BELAJAR MATEMATIKA MATERI BANGUN DATAR FASE B KELAS III SDN 11 LIMBOTO KABUPATEN GORONTALO - Sagita Shinta Pratiwi Dai; Lian G. Otaya; Asriyati Nadjamuddin (Institut Agma Islam Hamzanwadi NW Lombok TImur, 2026)
This study aims to examine whether there is an effect of the use of tangram media on the learning outcomes of mathematics on the material of flat shapes of grade III SDN 11 Limboto. This study uses a quantitative research type with a pre-experimental approach. The population in this study were all 26 students of grade III SDN 11 Limboto. Data collection techniques used observation, tests and documentation. The results of this study show that before the application of tangram media on the material of flat shapes phase B of grade III SDN 11 Limboto, as many as 3 students achieved the Minimum Completion Criteria (KKTP), while 23 other students had not achieved the KKTP. After learning using tangram media, there was an increase, where 22 students managed to achieve the KKTP score, and 4 students still did not meet the KKTP. The KKTP for the subject of Mathematics for grade III was set at 75. The results of the paired sample t-Test showed that the value of │ │=│7.74216│with a significance level of 5%. Because Because │ │=│7.74216│> value then the alternative hypothesis (H₁) is accepted and the null hypothesis (H₀) is rejected. This shows a positive influence of the use of tangram media on student learning outcomes in the material of flat shapes. This increase is also seen from the difference in average scores, namely the pretest of 57.42 and the posttest of 79.35, which indicates a significant increase in student understanding.